Strategy to Enhance Children’s Language Skills through Visual Flashcard Media: A Study on Early Childhood: Strategi Meningkatkan Kemampuan Berbahasa Anak melalui Media Visual Flashcard: Studi pada Anak Usia Dini - Husnul Laili; Ismayadi Ismayadi (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2025)
This study aims to enhance children's language skills through the use of visual flashcard media among Group A students at TK PGRI 27 Orong Rante, located in Mamben Baru Village, Wanasaba District, East Lombok Regency, during the 2024/2025 academic year. The research was motivated by the low level of children's language proficiency, as evidenced by the limited number of students categorized as BSH (Developing as Expected) and BSB (Very Well Developed). This study employed a Classroom Action Research (CAR) design implemented over three cycles, involving 34 children as research subjects. Data were collected through observation techniques to assess the development of children's language skills in each cycle. The findings revealed a significant improvement in language proficiency. Initially, only 5 children (15%) reached the BSH and BSB categories. This number increased to 24% in the first cycle, 30% in the second cycle, and finally reached 80% in the third cycle, surpassing the targeted 75%. These results indicate that the use of visual flashcard media is effective in improving the language skills of early childhood learners. Accordingly, this strategy is recommended for broader implementation in early childhood education settings.